DNA e Paleodistribuição potenciaç de Chiroxiphia pareola mostram diversificação e conexões históricas em florestas na América - Nascimento, Nayla Fábia Ferreira do (2016)
DNA and potencial paleodistribuition of Chiroxiphia pareola shows diversification and historical connections in South America rainforests. Rivers and Pleistocene forest refuges hypothese have been proposed as mechanisms to explain high diversity in Neotropical rainforests. Amazon and Atlantic forest disjunct species are good models to test these hypotheses, because are evidence of possible connections between these forests in South America. Therefore, we use molecular analyse and potential paelodistribution of a bird species with disjunct distribution, Chiroxiphia pareola, to test hypothese mentioned above. We aim to find evidences of possible diversification processes and/or bird populations expansion. We analyzed two mitochondrial and four nuclear genes of samples from sites along the species distribution. 179 location points and 19 climate variables were used to model distribution during the Current, Holocene, Last Glacial Maximum (LGM, 21 kya) and the Last Interglacial (LIG, 120 kya). Our results supported four evolutionary independent lineages in species polytypic C. pareola, which we recommend should be full species: C. regina, C. napensis, C. pareola and New taxon, the latter name recommended in this study. We support the proposal of rivers dynamics as effective diversification mechanisms in Amazon during Plio-Pleistocene. However, we do not corroborate effects of last maximum climatic fluctuations of the Quaternary. Although our results support forest refuges stability during Late Pleistocene in northeastern Atlantic forest, we do not support role of rivers as diversification mechanism in this region. We also suggest a connection route between the Amazon and Atlantic forests during Middle Pleistocene in region between São Francisco river and Chapada Diamantina, in northeastern Brazil.